Textbook outcome as a composite measure in oesophagogastric cancer surgery. Issue 6 (27th February 2017) - Busweiler, L. A. D.; Schouwenburg, M. G.; van Berge Henegouwen, M. I.; Kolfschoten, N. E.; de Jong, P. C.; Rozema, T.; Wijnhoven, B. P. L.; van Hillegersberg, R.; Wouters, M. W. J. M.; van Sandick, J. W.; ,
Abstract: Background: Quality assurance is acknowledged as a crucial factor in the assessment of oncological surgical care. The aim of this study was to develop a composite measure of multiple outcome parameters defined as 'textbook outcome', to assess quality of care for patients undergoing oesophagogastric cancer surgery. Methods: Patients with oesophagogastric cancer, operated on with the intent of curative resection between 2011 and 2014, were identified from a national database (Dutch Upper Gastrointestinal Cancer Audit). Textbook outcome was defined as the percentage of patients who underwent a complete tumour resection with at least 15 lymph nodes in the resected specimen and an uneventful postoperative course, without hospital readmission. Hospital variation in textbook outcome was analysed after adjustment for case‐mix factors. Results: In total, 2748 patients with oesophageal cancer and 1772 with gastric cancer were included in this study. A textbook outcome was achieved in 29·7 per cent of patients with oesophageal cancer and 32·1 per cent of those with gastric cancer. Adjusted textbook outcome rates varied from 8·5 to 52·4 per cent between hospitals. The outcome parameter 'at least 15 lymph nodes examined' had the greatest negative impact on a textbook outcome both for patients with oesophageal cancer and for those with gastric cancer. Conclusion: Most patients did not achieve a textbook outcome and there was wide variation between hospitals. Abstract : Novel approach to quality assessment